Predictors of Academic Performance among Entering Freshmen at a Private University in Lima - Grimaldo, Mirian (2023)
Introduction. One of the most significant indicators of quality in the academic endeavor of educational institutions is the academic performance of their student population. However, its study is complex, given its multi-causal nature. In view of the above, the general aim of this research was to identify those variables that could impact the academic performance (success or failure) of students admitted into a private university in Lima. Methodology. Two samples were taken corresponding to entrants of the two semesters of the academic year, for a total of 5040 participants (3515 from the first semester and 1889 from the second semester). The instruments applied were the Learning Strategies Questionnaire (Martínez Guerrero, 2004), the Vocational Self-Efficacy Sc ale (Carbonero Martín y Merino Tejedor, 2002), the Degree Maturity Questionnaire (Álvarez González et al., 2007), and the Test Anxiety Questionnaire (Valero Aguayo, 1999). Results. As part of the results of the logistic regression analysis, it was found that the variables that best predicted a failing weighted average were the following: a higher number of credits enrolled in leveling courses, male sex, lower score in self-efficacy beliefs, negative attitude towards the study program, a lower score in achievement motivation, and a higher score in exam anxiety. Discussion. It is concluded that academic performance can be explained from a set of motivational, emotional, and vocational variables, as well as some sociodemographic variables such as gender. Based on the results obtained, it is recommended to direct preventive actions toward those psychological and demographic aspects that are somehow associated with the performance of university entrants.